Efforts to Increase Student Interest, Motivation and Business Skills Through Entrepreneurship Courses at Mandalika University Of Education - Nuraeni, Nuraeni; Sudiarta, I Gusti Putu; Sutawijaya, I Made (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Entrepreneurship is a personality who dares to take risks to get financing through existing opportunities by acting as an inventor and playing a role in creating economic growth. Based on the description of student perceptions regarding the effectiveness of entrepreneurship course learning methods to increase interest, and motivation, and foster student business skills. The purpose of this study is to provide an overview of student perceptions regarding the effectiveness of entrepreneurship course learning methods to increase interest, and motivation, and foster student business skills in the Mandalika Education University Management Study Program. This study uses a qualitative research descriptive approach that uses the online survey method and the literature method as its data collection method. The results found that the perception of education students (learning methods) of entrepreneurship courses is considered effective for increasing interest, and motivation, increasing student business skills through practical activities (Maranatha Entrepreneurship Day), entrepreneurship seminars, and surveys to customers, and developing entrepreneurial learning methods (soft skills) and (live skills) can strengthen entrepreneurial interest and make entrepreneurship a promising career choice.